(untitled) (Journal of the Professional Association for Cactus Development, 1997)
In February 1997, I was invited to Crete for a 50th Celebration of the Mediterranean Diet. This celebration and analysis of the Mediterranean diet was initiated by the Rockefeller Foundation, which, in 1947, examined the food habits of 12 families for 1 month. The people in this region needed fruits that had good keeping qualities without refrigeration.